Motivational Interviewing Versus Cognitive Behavioral Group Therapy in the Treatment of Problem and Pathological Gambling: A Randomized Controlled Trial - Carlbring, Per (Taylor & Francis, 2009)
Pathological gambling is a widespread problem with major implications for society and the individual. There are effective treatments, but little is known about the relative effectiveness of different treatments. The aim of this study was to test the effectiveness of motivational interviewing, cognitive behavioral group therapy, and a no-treatment control (wait-list) in the treatment of pathological gambling. This was done in a randomized controlled trial at an outpatient dependency clinic at Karolinska Institute (Stockholm, Sweden). A total of 150 primarily self-recruited patients with current gambling problems or pathological gambling according to an NORC DSM-IV screen for gambling problems were randomized to four individual sessions of motivational interviewing (MI), eight sessions of cognitive behavioral group therapy (CBGT), or a no-treatment wait-list control. Gambling-related measures derived from timeline follow-back as well as general levels of anxiety and depression were administered at baseline, termination, and 6 and 12 months posttermination. Treatment showed superiority in some areas over the no-treatment control in the short term, including the primary outcome measure. No differences were found between MI and CBGT at any point in time. Instead, both MI and CBGT produced significant within-group decreases on most outcome measures up to the 12-month follow-up. Both forms of intervention are promising treatments, but there is room for improvement in terms of both outcome and compliance.